2014
DOI: 10.1007/s00894-014-2431-1
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of the per-6-amino-β-cyclodextrin as catalyst in synthesis of 2-aryl-2,3-dihydro-4-quinolones

Abstract: The synthesis of 2-aryl-2,3-dihydro-4-quinolones in the presence of per-6-amino-β-cyclodextrin (per-6-ABCD) as catalyst can improve selectivity and yield. The interaction between per-6-ABCD and benzaldehyde or o-aminoacetophenone plays an important role in this reaction. This paper studies the complexes of per-6-ABCD with benzaldehyde and o-aminoacetophenone using density functional theory (DFT) method. The reaction process is investigated by studying the energy of the reactants and the product. Hydrogen bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The typical counterplots of HOMO and LUMO of { 3CD@SiW 12 } obtained by PBE/LANL2DZ are shown in Figure a and Figure S14. The HOMO represents the ability to donate electrons, while the LUMO as an electron acceptor represents the ability to obtain electrons . Noticeably, the HOMO and LUMO of {SiW 12 } ⊂ CD (1:1) in { 3CD@SiW 12 } are both mainly spread around the POM molecule.…”
Section: Resultsmentioning
confidence: 95%
“…The typical counterplots of HOMO and LUMO of { 3CD@SiW 12 } obtained by PBE/LANL2DZ are shown in Figure a and Figure S14. The HOMO represents the ability to donate electrons, while the LUMO as an electron acceptor represents the ability to obtain electrons . Noticeably, the HOMO and LUMO of {SiW 12 } ⊂ CD (1:1) in { 3CD@SiW 12 } are both mainly spread around the POM molecule.…”
Section: Resultsmentioning
confidence: 95%
“…In 2014, a detailed DFT method about this per-6-ABCD-catalyzed asymmetric Mannich reaction was accomplished by the Liu group. 110 Their results showed that per-6-ABCD catalyst increases the nucleophilicity of o-aminoacetophenone and the electrophilicity of benzaldehyde and donor-acceptor interactions of the complex can increase the enantioselectivity of catalytic reactions.…”
Section: Asymmetric Mannich Reactionmentioning
confidence: 99%